2022
DOI: 10.1186/s40545-022-00498-w
|View full text |Cite
|
Sign up to set email alerts
|

A pilot assessment of the career and job satisfaction of the pharmaceutical workforce in Lebanon

Abstract: Background Lebanon has been recognized as a center for high-quality healthcare services in the Middle East because of its prestigious facilities certified by international bodies, competent health workers, and credible pharmaceutical sector. This study assessed the professional situation of the Lebanese pharmaceutical workforce upon graduation and entry to the job market. It also evaluated the satisfaction of pharmacists with the financial, physical, and psychological aspects of their job and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Thus, addressing these issues is crucial to maintaining service quality and patient safety. 38 Our study found that individuals with more than 2 children are nearly 4 times as likely to experience higher levels of stress compared to their childless counterparts. This aligns with findings from the United States, 41 where first year postgraduate pharmacy residents with children reported higher stress scores than those without children.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, addressing these issues is crucial to maintaining service quality and patient safety. 38 Our study found that individuals with more than 2 children are nearly 4 times as likely to experience higher levels of stress compared to their childless counterparts. This aligns with findings from the United States, 41 where first year postgraduate pharmacy residents with children reported higher stress scores than those without children.…”
Section: Discussionmentioning
confidence: 51%
“…Reduced personal accomplishment was higher than that found in health-system and hospital pharmacists but similar to what was reported in clinical pharmacists [ 11 , 12 , 26 ]. This finding is probably reflective of the impact that the economic collapse has had on mental health as well as the dissatisfaction with career opportunities for health system pharmacists in Lebanon [ 27 29 ]. It has been suggested that reduced personal accomplishment is likely to occur when pharmacists cannot focus on their clinical duties and have expectations to non-clinical duties such as working on tasks that can be performed by other members or student training without dedicated time.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, age was protective against burnout amongst clinical pharmacists in the US [ 11 ]. This difference is probably due to better career satisfaction and development opportunities available in the US and Europe [ 27 , 34 ]. More than half of our study represented early-career pharmacists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This number is considered one of the highest in the world, particularly for the BS Pharm (17.52/10,000 inhabitants up till the end of 2017 [ 10 ]), while the country lacks national policies that set the number of graduates per school according to the local needs. There are no precise data about the employability of graduates, but academic surveys demonstrate a decline in work opportunities over time [ 11 ].…”
Section: Introductionmentioning
confidence: 99%